Pengaruh Jumlah Wajib Pajak Orang Pribadi Terdaftar, Pemeriksaan Pajak dan Rasio Pencairan Tunggakan Pajak Terhadap Penerimaan Pajak Penghasilan Orang Pribadi - Dewi Oktaviani; Waluyo Waluyo (Universitas Multimedia Nusantara, 2015)
The objective of this research is to examine the effect of personal taxpayers, tax inspection disbursement of tax arrears ratio towards revenue from personal income tax. The object of this study is KPP Pratama Kosambi for the period 2011-2013. The samples in this study was determined based on convenience sampling. Number of samples taken are 36 data from January 2011 to December 2013. The testing method used in this research is multiple regression method. The data used in this study are secondary data. The results of this study are (1) number of individual taxpayers has significant effect towards revenue from personal income tax (2) tax inspection has significant effect towards revenue from personal income tax (3) tax arrears disbursement ratio has significant effect towards revenue from personal income tax. Keywords: number of individual taxpayers, tax inspection, rasio disbursement of tax arrears, revenue from personal income tax.